Nusantara Zaman Nabi Muhammad SAW: Kajian Terhadap Kondisi Nusantara Pra-Islam dan Masuknya Islam di Indonesia - Maghfiroh, Mauliana (Tasamuh: Jurnal Studi Islam, 2023)
Prophet Muhammad SAW is a great figure who initiated Islamic civilization in the world. His role as a religious and state leader has drawn admiration from various circles, including non-Muslims. Historical records prove his expertise in building civilization in Mecca, Medina and the surrounding areas to become civilized areas around the VI and VII centuries AD. In this case, much has been discussed about the civilization of the Arabian Peninsula during the time of the Prophet Muhammad SAW. However, related to the condition of Indonesia at that time there was still not much to discuss about it. This paper will specifically discuss the conditions of pre-Islamic Indonesia and the entry of Islam in Indonesia. Through qualitative methods with a historical approach it was found that the Islamic understanding of the archipelago had been formed through the traditions and beliefs of the Javanese people long before Islam came to the archipelago. In addition, the emergence of Nusantara civilization cannot be separated from the influence of Indian culture. The arrival of these Indian merchants brought changes to the belief system, introduced scripts and spearheaded the growth of Hindu-Buddhist-style royal institutions in the archipelago.